Proceedings of the 10th European Conference on Interactive TV and Video 2012
DOI: 10.1145/2325616.2325644
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on distant free-hand pointing

Abstract: In this paper we present a comparative study of free-hand pointing, an absolute remote pointing device. Unimanual and bimanual interaction were tested as well as the static reference system (spatial coordinates are fixed in the space in front of the TV) and novel body-aligned reference system (coordinates are bound to the current position of the user). We conducted a pointand-click experiment with 12 participants. We have identified the preferred interaction areas for left-and right-handed users in terms of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
(9 reference statements)
1
8
0
2
Order By: Relevance
“…As mentioned above, several research efforts have been performed for analyzing pointing tasks using Fitts' Law and THG [32,39,29,31,30]. Although we have found no reasons to estimate the time for this operator in a different way that the one in KLM, a value or equation is necessary for using P. However, we have not performed experiments for determining that value or equation.…”
Section: Pointing (P)mentioning
confidence: 91%
See 3 more Smart Citations
“…As mentioned above, several research efforts have been performed for analyzing pointing tasks using Fitts' Law and THG [32,39,29,31,30]. Although we have found no reasons to estimate the time for this operator in a different way that the one in KLM, a value or equation is necessary for using P. However, we have not performed experiments for determining that value or equation.…”
Section: Pointing (P)mentioning
confidence: 91%
“…The stroke time was computed as the period of time since a participant reached the button until s/he stopped pushing it. This value is approximated to those reported in [30].…”
Section: Tapping (T)mentioning
confidence: 96%
See 2 more Smart Citations
“…Bobeth et al [5] tested freehand menu selection for interactive TV with 4 different designs, and found that freehand gestures could be an appropriate way for older adults to control a TV. A selection task was also investigated in [29], and participants preferred freehand gestural pointing to using a handheld pointing device. Drawing different shapes in the air can also be used to select objects or menu items [2] with interactive TV, however, certain shapes are not easy to perform and remember, and have low recognition rates.…”
Section: Related Work 21 Gestural Interaction and Interactive Tvmentioning
confidence: 99%